Effect of plant extracts used as a methane mitigation additive on carcass fat content and fatty acid composition of South African Merino sheep - Webb, E.C. (Edward Cottington) (University of Pretoria, 2021)
Dissertation (MSc Agric Animal Science: (Animal nutrition))--University of Pretoria, 2021.